Polska literatura dziecięca w Chinach - Paterska-Kubacka, Agnieszka (Poznańskie Studia Polonistyczne. Seria Literacka, 2021)
Polish literature has been present in China since 1906. The first Polish literary text translated into Chinese was Latarnik (The Lighthouse Keeper) by Henryk Sienkiewicz. Contemporary fans of Polish novella and novel were reading indirect translations since the Chinese novelists, who did not speak Polish, usually based their translations on the Japanese versions. In my years of contact with Chinese culture and literature, I have never come across any mention of translations of Polish or Eastern European children’s literature. Once I started my research into this subject, I quickly learned what caused the lack of information on it. It turned out that it was quite difficult to find any credible information on what has been translated, in what volume it was published and what the reactions of young readers were. As a result, this article is merely an introduction to the research on Polish children’s literature in People’s Republic of China and focuses almost exclusively on latest publications, i.e. released in the twenty-first century. To a significant extent, it is based on data collected from people actively participating in promoting Polish culture in China via email. I received a lot of valuable data from Wojciech Widłak – one of the authors whose children’s books were published in China. The article is practically a short catalogue of books published on the Chinese market, but it also presents the few reviews I have managed to find in Chinese sources. There is also a presentation of the translators and it is worth noting that Polish children’s literature has been taken care of by the best among those studying Polish literature in China. I hope that this article will be the first of many on the position, popularity and reception of Polish children’s literature in China.